Oceanography an illustrated guide - Summerhayes, C. P.; Thorpe, S. A. (Manson Publishing, 1996)
With coverage ranging from history and instrumentation to the physical geography, meteorology, biology and chemistry of the sea and its ecosystems, this book provides a guide while promoting awareness of current ecological concerns governing man's relationship with the oceans.